Tissue Engineering Approaches in Skeletal Pediatric Disorders - Gentili, Chiara; Torre, Michele; Cancedda, Ranieri (European Journal of Pediatric Surgery, 2014)
The therapeutic use of stem cells is a very promising strategy in the area of regenerative medicine. The stem cell regenerative paradigm has been mostly based on the assumption that progenitor cells play a critical role in tissue repair by their plasticity and differentiation potential. However, recent works suggest that the mechanism underlying the benefits of stem cell transplantation might relate to a paracrine modulatory effect rather than the replacement of affected cells at the site of injury. Preclinical and clinical skeletal studies, conducted in animal and adult series, support the use of mesenchymal stem cells (MSCs) for bone healing in critical clinical situations. These results have led to an increasing number of papers reporting the use of MSCs in adult clinical trials, whereas only few papers reported the use of these cells in pediatric skeletal disorders, probably because of unknown long-term results and long-life consequences of cellular therapy. The exponential growth of knowledge in adult MSCs could be translated and applied to pediatric disorders. Pediatric osteoarticular diseases have an enormous potential to be treated by MSCs, as severe congenital bone or local cartilage defects, not responding to conventional surgery treatment, might be successfully treated by cellular therapy. Translating basic stem cell research into routine therapies is a complex multistep process which entails the managing of the expected therapeutic benefits with the potential risks in correlation within the existing regulations. Here, we reported the state of art on the use of MSC in skeletal pediatric disorders.
Keywords: stem cell; regenerative medicine; skeletal disorder; tissue engineering; pediatrics